Diseño de plan barrial para la preparación, prevención y respuesta ante emergencias en el sector oro negro de la ciudad de Neiva – Huila. (2020)
Emergencies resulting from natural, technical or social phenomena constitute a great challenge to the population that is normally unknown once it has happened; The following steps are fundamental to how to act in order to preserve your own life and that of a community as a response mechanism to said events. Objective: Design a neighborhood plan for emergency preparedness, prevention and response in the black gold sector of the city of Neiva - Huila. Research methodology: Empirical and analytical, the first step involves observation and analysis to identify risks, which seeks to define the variables to be studied, additionally the problem in all its dimensions. The methods used include quantitative and descriptive research. Results: identification of 11 threats in the Oro Negro neighborhood of the city of Neiva such as fires, electrical failures, floods, explosions, assaults, terrorism, riot, traffic accidents, seismic movements, droughts, atmospheric events and flooding due to infrastructure Conclusions: The development of the neighborhood plan will allow for greater capacity for response and management in the face of natural disasters